Effects of Alpha Lipoic Acid on Loss of Myelin Sheath of Sciatic Nerve in Experimentally Induced Diabetic Rats - Tasci, Irem; Demir, Caner Feyzi; Kuloglu, Tuncay (My University, 2018)
Objectives: Diabetic neuropathy is the most frequent chronic complication of diabetes. It may attack to sensory, motor or autonomous fibers. Varied mechanisms account for the development of diabetic neuropathy such as metabolic disorders, microvascular damages, neurotrophic support deficit, alternation in neuro-immune interactions, neural and glial cell apoptosis, and inflammation. Alpha lipoic acid (ALA) is a potent lipophilic antioxidant in vitro and in vivo conditions, which plays a main role as cofactor in many mitochondrial reactions, easily absorbed from gastointestinal tract and can easily cross the blood brain barrier (BBB). Apoptosis is an important mechanism of degenerative diseases, which is induced by some factors like hyperglycemia toxicity. In vivo and in vitro studies showed that hyperglycemia affected the cell survival and induced apoptotic changes in dorsal root ganglion neurons and Schwann cells. Methods: In this experiment we used a total of 28 rats. 14 rats were given 180mg/kg streptozotocin (STZ) dissolved by single intraperitoneally (i.p.) injection. Rats are divided into 4 groups; Control (group I), DM (group II), ALA (group III) and DM+ALA (group IV). Myelin sheaths of sciatic nerves were examined histologically for each group. Results: In the results of the histological examination, showed that loss of myelin sheath in sciatic nerves of rats while the group treated with ALA showed less myelin loss. Conclusion: This study might be suggested that ALA has a protective effect on peripheral neuronal cell damage generated with DM.
Keywords: alpha lipoic acid; diabetes mellitus; myelin sheath; sciatic nerve